Determinants of crowdfunding intention in a developing economy: ex-ante evidence from Bangladesh. Issue 6 (21st June 2020) - Munim, Ziaul Haque; Shneor, Rotem; Adewumi, Olugbenga Michael; Shakil, Mohammad Hassan
Abstract : Purpose: SME funding gaps in developing economies are substantial. Crowdfunding is an innovative way to raise funds that may be part of the solution for closing such gaps. The purpose of this study is to investigate the determinants of crowdfunding contribution intentions in the context of a developing country –Bangladesh. Design/methodology/approach: The authors collect data by using a structured questionnaire distributed through Facebook. The analysis is based on data collected from 252 valid responses and uses the ordered probit regression for estimation. For robustness, the authors also estimate the hypothesized model using ordered logistic regression and OLS regression finding identical results. Findings: The authors find that liking the campaign idea and positive media coverage of a crowdfunding campaign have a positive association with crowdfunding contribution intention. Surprisingly, personal relations, others' recommendation and the location of the campaign's owner were not significantly associated with crowdfunding contribution intention in our study. Moreover, respondents' location in Bangladesh (vs. abroad) and their age are positively associated with contribution intention, while education is negatively associated with intention. Originality/value: Earlier studies focused on the determinants of ex post crowdfunding intentions in developed and more mature crowdfunding markets. The authors contribute by examining ex ante crowdfunding contribution intentions in the developing economy of Bangladesh, which is at the market's inception stage.